Evaluating the management of building construction material waste in Kurdistan Region of Iraq - Agha, Mahmood Muhammed; Ayob, Mohd Fairullazi; Ibrahim, Mohd Shariffuddin (2021)
The video slides presentation was presented in the IIUM Research Day 2021 (IRD2021), an online a national event that organized by the Research ManagementCentre, International Islamic University Malaysia, Kuantan Campus.